Pengaruh Tepung Komposit Jagung (Zea mays) Dan Kedelai (Glycine max) Terhadap Tingkat Kekerasan Dan Daya Terima Biskuit - Yudistira, Ega; , Fitriana Mustikaningrum, S.Gz., M.Sc (2016)
The use of flour by the food processing industry in Indonesia include the materials for making bread, noodles, cakes, cookies and chips. One of the solution as the subtitute material for the flour which has a great potential to be developed is the use of corn and soybeans composite flour. Corn and soybeans can be used as a substitute for wheat flour in making biscuits. Protein level in the soybean flour is 34.9 g, meanwhile, protein level in the corn is 9.2 g per 100 g. It is expected to increase the level of nutrition in the biscuit by making it from soybeans and corn flour. This study was aimed to determine the level of hardness and receptivity of biscuits made of soybean and corn flour. The method of this study was an experimental research. The design of the study applied was a complete randomized design with three treatments on the soybean and corn flour, they were 50%: 50%, 60%: 40% and 70%: 30. The level of hardness was measured by using the instrument of Broxfield Texture Analyzer and the receptivity measurement was done by using using fondness test with 30 panelists. The data analysis of the study was done by using One Way Anova Test and then will be followed by Duncan Multiple Range Test (DMRT) if any significant result. Based on the results of Anova test, it is indicated that the hardness of soybean and corn flour biscuits of the three treatments, obtained p value 0.277. Based on ANOVA test, indicated that the p value on the receptivity of the soybean and corn flour biscuits on the colour is 0.930, aroma 0.223, flavor 0.165, texture 0.009, overall 0,105. There is no significant effect of the corn and soybean flour on the biscuit-making on the level of hardness and receptivity include color, aroma, taste and overall, however, there is a difference or influence on the texture of biscuit made of soybean and corn flour. Keywords : hardness, receptivity, corn flour, soybean flour, biscuits. Bibliography : 63 (1978-2015)